Representing Generations Through Slang: A Comparative Study of MTV and Tiktok in Indonesian Pop Culture - Ramadhan, Refan Gusti; Begum, Syahkira; Rosalinah, Yanti (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2026)
This article examines how slang shapes generational linguistic identity in Indonesia by comparing two media environments: MTV in the early 2000s and TikTok in the current digital era. Using sociolinguistic perspectives on media and youth identity, the study analyzes how each platform influences the creation, spread, and social meaning of slang. MTV, as a one-way broadcast medium, produced relatively stable slang tied to localized adaptations of global youth culture. In contrast, TikTok operates as a participatory, algorithm-driven space where slang changes quickly through abbreviation, blending, code-mixing, and sound alteration. These forms circulate virally and gain meaning through collective user practices. Despite differences in structure and pace, both eras show that slang functions as a marker of group belonging, humor, and generational distinction. The study demonstrates how shifting media infrastructures shape linguistic innovation and the ongoing negotiation of youth identity in Indonesian popular culture. Abstrak Artikel ini membahas bagaimana slang membentuk identitas linguistik generasi di Indonesia dengan membandingkan dua lingkungan media: MTV pada awal 2000-an dan TikTok pada era digital saat ini. Dengan menggunakan perspektif sosiolinguistik tentang media dan identitas anak muda, studi ini menganalisis bagaimana setiap platform memengaruhi penciptaan, penyebaran, dan makna sosial dari slang. MTV, sebagai media siaran satu arah, menghasilkan bentuk slang yang relatif stabil dan terkait dengan adaptasi lokal dari budaya anak muda global. Sebaliknya, TikTok berfungsi sebagai ruang partisipatif yang digerakkan algoritma, di mana slang berubah cepat melalui pemendekan, pencampuran, alih kode, dan perubahan bunyi. Bentuk-bentuk ini menyebar secara viral dan memperoleh makna lewat praktik pengguna. Meski berbeda dalam struktur dan kecepatan, kedua era menunjukkan bahwa slang berfungsi sebagai penanda kebersamaan kelompok, humor, dan pembeda antar generasi. Studi ini menunjukkan bagaimana perubahan infrastruktur media membentuk inovasi bahasa dan negosiasi identitas anak muda dalam budaya populer Indonesia.